2020
DOI: 10.3390/molecules25194378
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Circulating Lycopene in Low-Grade Chronic Inflammation: A Systematic Review of the Literature

Abstract: Background and aims: In recent years, it has become clear that low-grade chronic inflammation is involved in the onset and progression of many non-communicable diseases. Many studies have investigated the association between inflammation and lycopene, however, results have been inconsistent. This systematic review aims to determine the impact of circulating lycopene on inflammation and to investigate the effect of consuming tomato products and/or lycopene supplements on markers of inflammation. Methods: Eligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 96 publications
(172 reference statements)
0
18
0
1
Order By: Relevance
“…Patients with chronic pancreatitis had significantly lower plasma concentrations of antioxidants (selenium, vitamin A, vitamin E, beta-carotene, xanthine, beta-cryptoxanthine, and lycopene) compared with both control subjects and patients with recurrent acute pancreatitis [ 34 ]. Steenwijk et al [ 35 ] screened the publications which were published before March 2020. They suggested that there is little evidence that increasing tomato intake or lycopene supplementation decreases inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with chronic pancreatitis had significantly lower plasma concentrations of antioxidants (selenium, vitamin A, vitamin E, beta-carotene, xanthine, beta-cryptoxanthine, and lycopene) compared with both control subjects and patients with recurrent acute pancreatitis [ 34 ]. Steenwijk et al [ 35 ] screened the publications which were published before March 2020. They suggested that there is little evidence that increasing tomato intake or lycopene supplementation decreases inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a double blind, randomized, placebo-controlled crossover trial, in participants who had ingested a supplement containing a tomato extract (lycopene, phytoene, and phytofluene), no effect was observed on inflammation and oxidative stress despite the observed attenuation of the post-exercise increase in the muscle damage biomarker myoglobin [ 77 ]. Indeed, a recent systematic review [ 78 ] evaluated the effect of lycopene on the inflammation and the consumption of lycopene supplements and tomato products on the biomarkers of inflammation in humans. It was indicated that the lycopene levels were negatively affected during the inflammation.…”
Section: Biological Properties Of Tomato Bioactivesmentioning
confidence: 99%
“…Although an increase of lycopene levels (serum or plasma) was observed after intake of tomato /lycopene supplementation, there was no change in the inflammatory biomarkers. The authors of this study pointed that there is little evidence that the increase of consumption of tomato or lycopene supplements reduces the inflammation, but the depletion of lycopene could be one of the first indicators of low-grade inflammation [ 78 ].…”
Section: Biological Properties Of Tomato Bioactivesmentioning
confidence: 99%
“…As a result, the extraction of phenolic compounds, dietary fibers, and other bioactive compounds from these by-streams has been widely studied [61]. Compounds such as lycopene from tomato pomace [62,63] and various phenolic compounds from grape seed extract, apple peels, and orange peels [36,[64][65][66] are examples of compounds that can be valuable for the food industry for their health effects.…”
Section: Fruits Vegetables and Tubersmentioning
confidence: 99%